Aktualisasi Dakwah Dai Millennial di Ruang Maya: Perspektif Etika Dakwah dengan Studi Kasus di Kota Medan - Nashrillah MG (Universitas Islam Negeri Ar-Raniry, 2018)
This article presents the actualization of the preaching of millennial dai(preacher) group in cyberspace. The millennial da'i group is a young preacher who grows and develops together with advances in information technology, thus this group highly